PROBLEMATIKA HUKUM UMRAH KREDIT DALAM PANDANGAN IMAM SYAFII - Ismail; Sri Sudiarti (CENDEKIA: Jurnal Studi Keislaman, 2022)
One of the conditions for performing Umrah is being able. Able in the sense of being able to body and provision (cost). While credit is the same as debt. Imam Shafi'I in his book says no when doing worship to the Baitullah with debt. And some of these travel in Medan provide Umrah trips by way of credit or the so-called Umrah bailout in collaboration with the bank. This is where the problem arises in the opinion of Imam Shafi'i. First, what about the conditions for being able to perform Umrah and what is the reason for prohibiting Umrah by credit, so that you think so. Then how is the systematics in performing Umrah by way of credit. And finally, what are the opinions of people who have performed Umrah by credit regarding this matter. The method used is qualitative with a socio legal approach. Results of the author's findings are that many people perform Umrah with this credit method because of a lack of understanding of the meaning of istithaah from the conditions for Umrah even though the majority of Muslims in Medan follow Imam  Syafi’i. Meanwhile, Imam Shafi'i forbade Umrah with debt. Because credit is like debt. And also the desire to perform worship to Umrah which is like a lifestyle trend today. Therefore, many people want to perform Umrah by credit. There are even those who use the guarantee of the house they live in as collateral to perform Umrah by means of this credit. It will be a big problem if there are problems in paying the installments every month.